Strategy Implementation Of The Indirect Approach In The Battle Of Normandy And The Ukraine-Russia War - Reghina Rizqy Syifaranie; Lukman Yudho Prakoso; Hafidz Kuncoro Jati; Puja Sari Putri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
The Russia-Ukraine War is still rolling today, potential and factual threats can make the war even more late. In building a defense and security system the best can be done by studying the history of battles in the past. One of them is the Battle of Normandy which was fought by America and its allies with Germany in northern France. This article aims to gain benefits to build a better strategy for sea defense operations from the events of the Battle of Normandy and the Russia-Ukraine war. The method used is qualitative by using literature as a source of data. The results of the analysis and discussion carried out on these two events, the researcher found that both carried out the concept of implementing the Indirect Approach strategy echoed by Sir Basil Liddell Hart in which Ukraine carried out an unexpected attack on the Russian cruiser, Moskva, which caused the sinking the ship. So that the concept of the Indirect approach strategy carried out by America and its allies in the 2nd World War is still relevant to strategic maritime defense operations in the 21st century.